The Influence of Financial Literacy, Ease and Risk in Transaction Using Financial Technology - Sumussang , Indriani Lolo; Jaya, Amir; Todingbua , Manuel A. (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
This study aims to analyze the influence of financial literacy, ease of use, and risk on transactions using Financial Technology (Fintech) among students of Universitas Kristen Indonesia Paulus. This study uses a quantitative approach with a survey method and purposive sampling technique. A total of 96 respondents were sampled, and the data were analyzed using the SEM model with the help of SmartPLS. The results of the study indicate that financial literacy and ease of use do not have a significant effect on transactions using fintech. In contrast, the risk variable has a significant and positive effect. This finding indicates that students consider the risk aspect seriously before making digital transactions. This emphasizes the importance of transparency and security assurance from fintech service providers in building user trust. The implications of this study highlight the need for fintech providers and educational institutions to improve students' understanding of the risks of digital transactions and strengthen service security systems. This study contributes to the literature on fintech user behavior among the younger generation, especially in the context of higher education. Keywords: Financial Literacy, Convenience, Risk, Transaction, Fintech, Students